1977
DOI: 10.1126/science.195.4275.283-a
|View full text |Cite
|
Sign up to set email alerts
|

Azaarenes in Recent Marine Sediments

Abstract: Chemical fractionation and mass spectral probe distillation reveal the presence in recent marine sediments of a complex assemblage of nitrogen-containing aromatic compounds. These azaarenes range from three- to eight-membered rings, with homologs containing up to eight alkyl carbons. In their composition, and presumably in their origin in natural fires, they resemble the aromatic hydrocarbons found in the same sediments. The analytical, geochemical, and environmental implications of these findings are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 7 publications
2
40
0
Order By: Relevance
“…Numerous studies have concluded that incomplete combustion is the predominant source of PAHs (Lee et al, 1981; and references therein), azaarenes (Blumer et al, 1977), and BC (Grundel et al, 1984) in the environment. Exceptions include petroleum seeps or spills, and petrogenic sources (Dickens et al, 2004a,b;Dittmar and Koch, 2006).…”
Section: Limitations On Cars Quantification and Source Apportionment mentioning
confidence: 97%
“…Numerous studies have concluded that incomplete combustion is the predominant source of PAHs (Lee et al, 1981; and references therein), azaarenes (Blumer et al, 1977), and BC (Grundel et al, 1984) in the environment. Exceptions include petroleum seeps or spills, and petrogenic sources (Dickens et al, 2004a,b;Dittmar and Koch, 2006).…”
Section: Limitations On Cars Quantification and Source Apportionment mentioning
confidence: 97%
“…K ow , K oc , K oa , K d and pK a than the homocyclic PAHs (Broholm et al 1999;Anyanwu and Semple 2015a, b). Furthermore, their concentrations in environmental matrices seem to be variable compared to PAHs; for example, concentrations of N-PAHs found in the environment are reported to be 1 or 2 orders of magnitude lower than the homologous PAH (Blumer et al 1977), but their biological effects can be of similar in magnitude (Dijkman et al 1997;Pašková et al 2006). However, De Voogt and Laane (2009) recorded total concentrations ranges almost equal to 1 order of magnitude higher than their homocyclic analogues.…”
Section: Introductionmentioning
confidence: 97%
“…However, soil levels of total N-PAC in the range 10-100 ppm do not appear to be unrealistic at contaminated sites. Furthermore, N-PAC are widely distributed in the environment and occur at levels that are 1-10% of those of PAH [6,7]. Besides the use of lar and creosote [&lo], the sources are combustion processes [ll].…”
Section: Introductionmentioning
confidence: 99%